1992
DOI: 10.3109/02844319209016010
|View full text |Cite
|
Sign up to set email alerts
|

Cephalometric Measurements in Patients with Pierre Robin Syndrome and Isolated Cleft Palate

Abstract: To compare craniofacial structure and growth, two standard lateral cephalograms of 35 children with Pierre Robin syndrome and 30 age and sex matched children with isolated cleft palate were taken at two different ages. The mean (SD) age of the children with Pierre Robin syndrome was 9.5 (3.0) years and of the children with isolated cleft palate 7.1 (1.1) years at the start of the follow up period. The follow up time in the first group was 4.3 (1.6) and in the second group 3.8 (2.7) years. There were no signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
43
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 5 publications
6
43
0
Order By: Relevance
“…13,29 Robin sequence infants might lack an intrinsic potential to grow out to values of healthy counterparts. [30][31][32][33][34] No studies have described the influence of mandibular distraction osteogenesis on craniofacial features in Robin sequence infants after longer follow-up. We demonstrated that, after a mean follow-up of 6.8 years, Robin sequence infants had a significantly shorter mandibular length compared with Robin sequence infants who did not undergo mandibular distraction osteogenesis.…”
Section: Discussionmentioning
confidence: 97%
“…13,29 Robin sequence infants might lack an intrinsic potential to grow out to values of healthy counterparts. [30][31][32][33][34] No studies have described the influence of mandibular distraction osteogenesis on craniofacial features in Robin sequence infants after longer follow-up. We demonstrated that, after a mean follow-up of 6.8 years, Robin sequence infants had a significantly shorter mandibular length compared with Robin sequence infants who did not undergo mandibular distraction osteogenesis.…”
Section: Discussionmentioning
confidence: 97%
“…To determine the size and/or position of the mandible in the RS child, a number of measurement methods have been described in literature, such as the jaw index, plain x-rays, and computed tomgraphy scans (Figueroa et al 1991;Laitinen and Ranta 1992;van der Haven et al 1997;Vegter et al 1999;Daskalogiannakis et al 2001). In this survey, the majority of the respondents relied on clinical sight in the determination of an (ab)normal size and/or position of the mandible.…”
Section: Discussionmentioning
confidence: 99%
“…This deficit can be seen from the youngest to the oldest examined children. By visual analysis of the position of the Laitinen and Ranta 6 have reported some maxillary retrusion compared with healthy Scandinavian children using cephalometry. More precise information, however, is missing.…”
Section: Vertical Directionmentioning
confidence: 97%